Political Constitution of Peru: Norms related to peasant communities, native communities, peasant rondas and other community social organizations - Perú, República del (2002)
Title 1: Of the person and society, chapter 1: Fundamental rights of the person, article 1: The defense of the human person and respect for their dignity are the supreme goal of society and the State.